2017
DOI: 10.1186/s12882-017-0605-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin-converting enzyme inhibitors and angiotensin receptor blockers on cardiovascular events and residual renal function in dialysis patients: a meta-analysis of randomised controlled trials

Abstract: BackgroundThe role of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) reducing risk of cardiovascular events (CVEs) and preserving kidney function in patients with chronic kidney disease is well-documented. However, the efficacy and safety of these agents in dialysis patients is still a controversial issue.MethodsWe systematically searched MEDLINE, Embase, Cochrane Library and Wanfang for randomized trials. The relative risk (RR) reductions were calculated with a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…While RAAS blockade raises concerns of hypotension and hyperkalemia, these side effects may be outweighed by potential increased survival and cardiac function. Combination ARB and ACEI therapy appears to decrease the loss of residual renal function in patients on PD patients . There is no evidence that ARB and ACEI treatment differs with regard to myocardial infarction, stroke, cardiovascular death, and all‐cause mortality .…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…While RAAS blockade raises concerns of hypotension and hyperkalemia, these side effects may be outweighed by potential increased survival and cardiac function. Combination ARB and ACEI therapy appears to decrease the loss of residual renal function in patients on PD patients . There is no evidence that ARB and ACEI treatment differs with regard to myocardial infarction, stroke, cardiovascular death, and all‐cause mortality .…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Combination ARB and ACEI therapy appears to decrease the loss of residual renal function in patients on PD patients. 100 There is no evidence that ARB and ACEI treatment differs with regard to myocardial infarction, stroke, cardiovascular death, and all-cause mortality. 100 In an earlier meta-analysis, ACEI and ARB treatment individually reduced LV mass in HD patients, but were not associated with reduction of cardiovascular events.…”
Section: Pharmacological Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Blockade of the renin‐angiotensin system with angiotensin‐converting enzyme inhibitors and/or angiotensin receptor blockers has been demonstrated in several randomized controlled trials to help preserve RKF in PD patients . However, while there is some observational evidence that the use of these agents is associated with preservation of RKF in HD patients, the only prospective randomized controlled trial performed in HD patients found that irbesartan treatment for 1 year did not affect the decline in GFR or urine volume …”
Section: Rkf Measurementmentioning
confidence: 99%
“…Because of this, there are a plethora of antihypertensives available to physicians. First line drugs in management include angiotensinconverting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARBs), especially indicated for diabetic patients due to their renoprotective effects [3][4]. However, sometimes due to the adverse effects of these medications, as can be witnessed with other medications, their use is limited.…”
Section: Introductionmentioning
confidence: 99%